Ownership structure, dividend policy and shareholders wealth among listed non-financial firms in Nigeria (Journal of Economic Research & Business Administration, 2024)
In the field of corporate finance, there is still disagreement over whether ownership structure and dividend policy have an impact on shareholders' wealth. Thus, between 2012 and 2021, this study aims to empirically demonstrate the combin ed effects of ownership structures and dividend policies on the stockholder wealth of listed non-financial companies in Nigeria. The study's population comprised the non-financial enterprises registered on Nigerian Exchange Group. Purposive sampling was used to choose a total of 54 firms for the sample size. For this study, an expo-facto research design was used. The Nigerian Exchange Group's publications and the publicly available financial statements of the selected companies provided secondary data for the study. The panel data regression model was the analysis technique used. The combined impact of ownership structure and dividend policy on shareholders' wealth was found to be positive and significant. The outcome supports the agency theory's contention that ownership structure is an oversight tools that can be used to curtail management's opportunistic behavior while regular dividend payments provide the company a favorable impression in the eyes of investors, they also enable the company to raise capital through the issuance of additional shares, which increases shareholder value. Therefore, the study suggested that policy makers for Nigerian non-financial enterprises restructure their ownership structure and dividend policy in a way that will promote strict oversight of operations and effective resource management, ultimately increasing the value of the company for its shareholders. Other economic sectors were not taken into consideration; the analysis is limited to Nigerian listed non-financial enterprises.Key words: Non-financial firms; agency theory; dividend policy; shareholders wealth.